Understanding the adsorption of newly Benzylidene-aniline derivatives as a corrosion inhibitor for carbon steel in hydrochloric acid solution: Experimental, DFT and molecular dynamic simulation studies - M.E. Belghiti; S. Bouazama; S. Echihi; A. Mahsoune; A. Elmelouky; A. Dafali; K.M. Emran; B. Hammouti; M. Tabyaoui (Arabian Journal of Chemistry, 2020)
Corrosion inhibition of carbon steel in hydrochloric acid solution was inspected using newly Benzylidene-aniline derivatives namely: (E)-N(2-Chlorobenzylidene)-2-Fluorobenzenamine (NCF) and (E)-N(2-Chlorobenzylidene)-3-Chloro-2-Methylbenzenamine (NCCM), by potentiodynamic polarization and electrochemical impedance spectroscopy (EIS) techniques. The experimental results showed that both NCF and NCCM are good inhibitors for carbon steel in 1 M HCl. The inhibition efficiency increases with inhibitors concentration rise, reaching a value up to 89.72% at 10−3 M for the inhibitor NCF. Electrochemical impedance data show a frequency distribution of the capacitance, simulated as constant phase element (CPE). Polarization curves study revealed that both inhibitors are mixed type. The adsorption on the carbon steel surface follows Langmuir isotherm model with negative values of ΔGads0. Thermodynamics data for the adsorption process are calculated and discussed. The effect of molecular structure on inhibition efficiency was investigated by quantum chemical calculations using density function theory (DFT). Furthermore, Monte Carlo simulation technique incorporating molecular mechanics and molecular dynamic was applied to search for the best configurationally space for (NCCM or NCF)/100H2O/α-Fe2O3 (1 1 1) systems. The results indicate that the adsorption energy of NCF was greater than NCCM which is in accordance with the experimentally determined inhibition efficiency. Keywords: Corrosion inhibition, HCl, Benzylidene-aniline, Carbon steel, Electrochemical techniques, DFT, Molecular Dynamics Simulation